Contemporary Trends in Human Factors and Ergonomics within Engineering Research - Adelino, Muhammad Ilham; Zadry, Hilma Raimona; Susanti, Lusi (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This review explores human factors and ergonomics (HFE) in the engineering subject areas and analyzes research over the last five years across physical, cognitive, and organizational ergonomics and is associated with the Industrial Revolution era. This review aims to identify existing trends in HFE research related to the Industrial Revolution. This study used a systematic four-step methodology and drew from the Science Direct and Scopus databases. The methodology involves conducting a careful literature search, selecting pertinent and suitable literature references, conducting bibliometric analysis, and participating in qualitative discussions. A total of 353 articles are identified for further analysis. Our findings indicate that the current state of Human Factors and Ergonomics (HFE) research remains largely situated within the research paradigm of the Industrial Revolution 3.0 era. Investigations oriented towards the Industrial Revolution 4.0, such as integrating machine learning and artificial intelligence into physical, cognitive, and organizational ergonomics, are still limited. The insufficient adoption of these advancements underscores the necessity for ongoing development of HFE research to leverage these advancements in order to align with the trajectory towards Industry 4.0.